Use of synthetic glycoconjugates containing the Mycobacterium leprae specific and immunodominant epitope of phenolic glycolipid I in the serology of leprosy. - Brett, S J (1986)
The high specificity of phenolic glycolipid I (PG-I) in the identifying individuals with leprosy appears to be attributable to the species-specific trisaccharide region of the molecule. Synthetic glycoconjugates were produced by coupling the corresponding terminal mono- or disaccharide to bovine serum albumin by reductive amination. Conjugates which contained only the terminal sugar maintained in its pyranose form, the terminal disaccharide with only the terminal sugar in its pyranose form and the terminal disaccharide with both the 3,6,di-o-Me-glucose and 2,3,di-o-Me-rhamnose sugars in their pyranose forms, were all highly active in the enzyme-linked immunosorbent assay (ELISA) and showed good concordance with native PG-1 in analysis of sera from leprosy patients. The antibody levels to the glycoconjugates in tuberculosis patients and patients with other mycobacterial infections were not significantly different from the levels in normal healthy control subjects. A few of the leprosy sera showed much stronger binding to conjugates which contained the disaccharide with both sugars in the pyranose form than to conjugates with only the terminal sugar in its pyranose form. Therefore a synthetic conjugate which contains the intact disaccharide region of PG-I may provide the most sensitive antigen for the large scale serodiagnosis of leprosy.